2020
DOI: 10.1002/2211-5463.12911
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin increases migration and invasion of rat placental trophoblast cells

Abstract: Preeclampsia (PE) is a hypertensive disorder of pregnancy. Early diagnosis of PE is currently contingent on regular prenatal physical examinations and may be facilitated by identification of novel diagnostic markers. Transthyretin (TTR), also known as prealbumin, is primarily responsible for maintaining the normal levels of thyroxine and retinol binding protein. The expression of TTR is lower in patients with severe PE as compared with healthy controls. Here, we examined the suitability of TTR as a diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Eventually, this decreases placental blood perfusion, leading to preeclampsia. Therefore, the apoptosis and migration of placental trophoblasts are important processes contributing to the development of preeclampsia ( 23 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, this decreases placental blood perfusion, leading to preeclampsia. Therefore, the apoptosis and migration of placental trophoblasts are important processes contributing to the development of preeclampsia ( 23 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The methods for the transwell migration and invasion assays have been reported in a previous study [ 29 ]. For the migration assay, the upper transwell insert (8-μm pore size; Corning Costar, Cambridge, MA, USA) was directly placed in one well of a 24-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for the transwell migration and invasion assays have been reported in a previous study [29].…”
Section: Transwell Migration and Invasion Assaysmentioning
confidence: 99%
“…Therefore, exploring the metastatic and invasive properties of trophoblast cells is crucial for the progression of PE. Studies have shown that promoting the migration and invasion of rat placental trophoblast cells helps control gestational hypertension [ 21 ]. Invasive deficiency of trophoblast cells and impaired spiral arterial remodeling underlie fetal growth restriction and preeclampsia-like symptoms in hypertensive rats [ 22 ].…”
Section: Discusssionmentioning
confidence: 99%